Role of health literacy and primary health-care access in self-care management of hypertension - Pundla Nagarjuna; Vimal Kumar; Dharamjeet Singh Faujdar; Arun Kumar Yadav (Wolters Kluwer Medknow Publications, 2023)
Background: Globally, hypertension is the leading risk factor for men and women and the largest contributor to premature deaths and diseases in India. Health literacy (HL) and health-care access are important determinants for self-care management of hypertension. Objectives: The purpose of this study was to estimate the prevalence of HL, health-care access, and their importance in the self-care management of hypertension. Materials and Methods: A community-based cross-sectional study was conducted among 104 known hypertensive patients for 2 months from May to June 2022. Data were collected by face-to-face interviews using a pretested, preformed, and validated questionnaire, and tabulated and analyzed using Microsoft Excel and SPSS version 20 software. Results: Most of the participants (80, 76.9%) have low levels of HL. However, more than half of the (62, 59.6%) participants were satisfied with their access to primary health care. The age of the participants ranged from 38 to 80 years, and half of them (54, 51.9%) were middle-aged adults. The majority (66, 63.5%) of the patients belonged to lower-middle socioeconomic status, and 15.4% (16) were living alone. We found poor HL, and primary health-care access is statistically significantly associated with poor self-care management. Conclusion: Our findings confirm that HL and access to primary health care are crucial factors in the self-care management of hypertension in hypertensive patients.